The Moral Message of Lafadz Insyaallah in View of Linguistics and Mathematics - Himatul Istiqomah (AJIS: Academic Journal of Islamic Studies, 2019)
Insyaallah is often used in daily conversation. Consequently, its essence does not get the attention from majority of speaker, because it belongs to ususal matter. Through the tadabbur method with an integrative approach between Insyaallah in the Al-Quran in Linguistics and rules of Logic in Mathematic, this research aims to reveal its moral messages, in order to understand its function. The results in this research indicate that Insyaallah which wasoriginally like Implication in the rules of Logic, after being reanalyzed it waslike Biimplication. Insyaallah does not mean if God will, but if only if God will. This presents a positive moral message. Humans who donot have anypower are factually motivated not to despair of Gods mercies. So they are able to fulfillcertain consequences when God determines His antecedents. In other word, the actual fuction of Insyaallah teaches people to think and act positively, both when interacting with other humans and the Creator.